Organizational Resilience And Sustained Competitive Advantage: The Mediating Role of Organizational Learning In Higher Education Institutions - Widiantoro, Didik; Shahadan, Md Azman; Nugroho, Sigit; Sari, Meyritha Trifina; Fitriyana, Nur (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
In an era of disruption marked by rapid digital technological advancement and increasing demands for educational quality, private universities in Indonesia face significant challenges in sustaining their competitive advantage. This study aims to examine the effect of organizational resilience on sustained competitive advantage, with organizational learning serving as a mediating variable. A quantitative approach was employed, involving 191 respondents consisting of lecturers and structural leaders at private higher education institutions. Data were collected using a questionnaire and analyzed through Jamovi. The results reveal that organizational resilience has a positive effect on sustained competitive advantage (β = 0.154, p = 0.044), as well as on organizational learning (β = 0.492, p < 0.001). Additionally, organizational learning significantly influences sustained competitive advantage (β = 0.298, p = 0.004) and partially mediates the relationship between organizational resilience and sustained competitive advantage (Indirect Effect = 0.147, p = 0.005). These findings underscore the strategic importance of organizational learning as a bridge that transforms resilience into long-term competitive advantage in the private higher education sector.Keywords: Organizational Resilience, Sustained Competitive Advantage, Organizational Learning, Higher Education Institutions